2001
DOI: 10.1039/b008039j
|View full text |Cite
|
Sign up to set email alerts
|

How polar are room-temperature ionic liquids?

Abstract: The solvent strength and polarity of four imidazolium and pyridinium based ionic liquids, as measured using two different fluorescent probes, indicate that these liquids are more polar than acetonitrile but less polar than methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
315
0
6

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(351 citation statements)
references
References 14 publications
30
315
0
6
Order By: Relevance
“…Different investigations of solvent-solute interactions in ionic liquids using solvatochromic dyes have been reported. 134,135 This is in agreement with the ionic liquid solvent effect described in the Diels-Alder reactions of cyclopentadiene with methyl acrylate. 136 The endo/ exo selectivity, which may be viewed as being dependent on the polarity of the solvent, is high (6.1:1) when using [BMIM] .…”
Section: Inorganic Synthesis In Ionic Liquidssupporting
confidence: 76%
“…Different investigations of solvent-solute interactions in ionic liquids using solvatochromic dyes have been reported. 134,135 This is in agreement with the ionic liquid solvent effect described in the Diels-Alder reactions of cyclopentadiene with methyl acrylate. 136 The endo/ exo selectivity, which may be viewed as being dependent on the polarity of the solvent, is high (6.1:1) when using [BMIM] .…”
Section: Inorganic Synthesis In Ionic Liquidssupporting
confidence: 76%
“…34,35 In fact, the polarities of imidazolium-based ILs were found to be similar to that of short chain alcohols. 36 A review regarding the polarity of ILs was presented recently by Reichardt. 37 It should, nevertheless, be kept in mind that the solvent parameters are dependent on the molecule probe employed 34 and are particularly relevant for these nanostructured fluids.…”
Section: Resultsmentioning
confidence: 99%
“…The most common empirical solvent polarity scale relies on the solvatochromic behavior of various dyes in different solvent systems (15)(16)(17)(18). In terms of solvent strength and selectivity, this method was also used to classify single-and mixed-solvent LC systems (20).…”
Section: Description and Propertiesmentioning
confidence: 99%
“…All results from this approach have indicated that IL solvents have polarities close to those of short-chained alcohols. Nevertheless, it is well known that two ILs with different cation-anion combinations can have significantly different effects on reaction rates, product ratios, chromatographic retention, and extraction selectivity (1,3,18). This polarity-based parameter, however, provides a "weighted average" of all solvation interactions and fails to discriminate among the various properties of ILs with different cation-anion combinations.…”
Section: Description and Propertiesmentioning
confidence: 99%